2021
DOI: 10.1002/tqem.21726
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine toxicity to Handroanthus heptaphyllus, a nontarget species from a Brazilian biome threatened by agriculture

Abstract: The economic basis of the Brazilian midwest is agriculture, concentrating most of the grain production in the country. With the purpose of increasing yield, farmers have intensified land use and the use of atrazine among other pesticides, which can supposedly compromise human health and photosynthetic metabolism of plant species from Cerrado, such as Handroanthus heptaphyllus. The aim of this study was to determine experimentally the sensitivity level of H. heptaphyllus to atrazine, by measuring gas exchange, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In this study, the gradual increase in DI 0 /RC with increasing ATZ concentration suggested that partial excitation energy was dissipated in nonphotochemical processes, especially achieving signi cant differences at higher levels of ATZ (≥ 1.0 mg•L − 1 ). The signi cant increase in the nonphotochemical quenching was also observed by Silva et al (2021) in determining the sensitivity level of Handroanthus heptaphyllus to ATZ. Though this increase diminished the fraction of energy delivered to PS II centers, it played an important role in the mitigation against photodamage, which re ected the tolerance of I. pseudacorus to ATZ by activating the photoprotective responses (Cazzaniga et al 2013).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In this study, the gradual increase in DI 0 /RC with increasing ATZ concentration suggested that partial excitation energy was dissipated in nonphotochemical processes, especially achieving signi cant differences at higher levels of ATZ (≥ 1.0 mg•L − 1 ). The signi cant increase in the nonphotochemical quenching was also observed by Silva et al (2021) in determining the sensitivity level of Handroanthus heptaphyllus to ATZ. Though this increase diminished the fraction of energy delivered to PS II centers, it played an important role in the mitigation against photodamage, which re ected the tolerance of I. pseudacorus to ATZ by activating the photoprotective responses (Cazzaniga et al 2013).…”
Section: Discussionmentioning
confidence: 55%
“…These results suggested that this plant species exhibited relatively high tolerance to ATZ stress at this level through enhancing the electron supply from P 680 to Q A and energetic connectivity. To minimize damage to the photosynthetic apparatus, excess energy can be dissipated as nonphotochemical processes, including thermal dissipation (Silva et al 2021). In this study, the gradual increase in DI 0 /RC with increasing ATZ concentration suggested that partial excitation energy was dissipated in nonphotochemical processes, especially achieving signi cant differences at higher levels of ATZ (≥ 1.0 mg•L − 1 ).…”
Section: Discussionmentioning
confidence: 65%
“…The species has significant ecological and economic value, making it useful for afforestation and urban landscaping projects (Berghetti et al, 2021). They are also commonly used in reforestation programs and to restore degraded areas (Silva et al, 2021). The timber from this species is used in construction due to its high density, strength, and malleability (Parcianello et al, 2021).…”
Section: Introductionmentioning
confidence: 99%